Leading to Achieve Social Change: An Interview with Ruth Hunt, Former Chief Executive Officer of Stonewall. (January 2021) - Bolden, Richard; Williams, Rachel; O'Regan, Nicholas
In this interview, Ruth Hunt, former CEO of the lesbian, gay, bi, and trans equality charity Stonewall and now crossbench peer at the House of Lords, discusses her approach to leadership for social change. She considers the changing context of LGBT rights, her motives for joining the organization, experiences and learning from leading change on this agenda, and the challenges of addressing power, privilege, and embedded cultural norms in order to create a truly inclusive workplace. Key themes include managing the tensions between an assimilation and liberation approach to social change, promoting intersectionality and positive action to enhance inclusion, the challenges and opportunities of sharing power and the skills of facilitation, boundary-spanning and working relationally that constitute the everyday practice of leadership in complex and contested landscapes. A commentary is provided that highlights links to and implications for leadership, management and organization scholarship, education and practice.